2014
DOI: 10.1007/s00429-014-0821-x
|View full text |Cite
|
Sign up to set email alerts
|

Allen mouse brain atlases reveal different neural connection and gene expression patterns in cerebellum gyri and sulci

Abstract: The recently released Allen Mouse Brain Connectivity Atlas provides a comprehensive mouse brain neuronal connectivity map from brain-wide injection sites via anterograde tracers coupled with serial two-photon tomography. In addition, the Allen Mouse Brain Atlas offers a genome-wide gene expression database built upon a series of in situ hybridization images, covering comprehensive expression energy of over 4,000 genes in coronal sections and over 20,000 genes in sagittal sections across the whole mouse brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…A previous study indicated that the cytoarchitecture of gyri and sulci is greatly different in the human brain [51] . Additionally, a significant difference between gyri and sulci in the axonal connectivity function and gene expression was found both in animals and humans [27,52] . A multimodal diffusion tensor imaging/ fMRI study [27] suggested that gyri are more related to longer connections that exchange information among distant structurally connected cortical regions via dense fibers, while sulci are more related to shorter connections that communicate directly with their neighboring gyri and indirectly exchange information with remote regions through gyri.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that the cytoarchitecture of gyri and sulci is greatly different in the human brain [51] . Additionally, a significant difference between gyri and sulci in the axonal connectivity function and gene expression was found both in animals and humans [27,52] . A multimodal diffusion tensor imaging/ fMRI study [27] suggested that gyri are more related to longer connections that exchange information among distant structurally connected cortical regions via dense fibers, while sulci are more related to shorter connections that communicate directly with their neighboring gyri and indirectly exchange information with remote regions through gyri.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that cortical gyri might participate more in multiple and heterogeneous functional processes than sulci in specific task performances, and might be consistent with our previous study based on resting state fMRI data demonstrating that gyri are global functional connection centers and sulci are local functional units (Deng et al, 2014). As demonstrated in Introduction, there have been several findings reporting the structural/functional differences between gyri and sulci (Nie et al, 2012; Takahashi et al, 2012; Chen et al, 2013; Zhang et al, 2014; Zeng et al, 2014; Deng et al, 2014). For the first time (as far as we know), we demonstrated the functional difference during a specific task performance (i.e., THFRs distribution difference) between gyri and sulci in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in human brain mapping from both micro- and macro- scale to investigate the possible structural/functional differences between gyri and sulci, and several interesting findings have been reported (Nie et al, 2012; Takahashi et al, 2012; Chen et al, 2013; Zhang et al, 2014; Zeng et al, 2014; Deng et al, 2014). For instances, a recent micro-scale study (Zeng et al, 2014) based on recently released Allen Mouse Brain Atlas demonstrated that the cerebellum gyri and sulci of rodent brains are significantly different in both axonal connectivity and gene expression patterns. For macro-scale data analysis, our recent studies (Nie et al, 2012; Chen et al, 2013) demonstrated that the termination of streamline fibers derived from diffusion magnetic resonance imaging (dMRI) (e.g., diffusion tensor imaging (DTI) and high angular resolution diffusion imaging (HARDI)) concentrate on gyrus in human, chimpanzee, and macaque brains.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the axonal pushing hypothesis of cortical folding has been proposed, which implies that gyri should have a higher density of fiber connection than sulci (Chen et al, 2013; Li et al, 2015; Nie et al, 2012). In parallel with prior findings in macroscale neuroimaging studies in primates, a recent study based on Allen Mouse Brain Connectivity Atlas and the Allen Mouse Brain Atlas found that the cerebellum gyri and sulci of rodent brains are significantly different in both axonal connectivity and gene expression patterns (Zeng et al, 2015). …”
Section: Introductionmentioning
confidence: 52%
“…Thanks to recent advances in multimodal neuroimaging techniques, such as high angular resolution diffusion imaging (HARDI) (Tuch et al, 2002) and diffusion tensor imaging (DTI) (Mori and Zhang, 2006), the neuroscientific communities have made remarkable progresses in understanding the underlying structural originations of cerebral cortex via fiber wiring diagrams and functional activities with decent spatial and temporal resolutions. In particular, several inspiring findings from anatomic/structural/functional perspectives have been reported that there are intrinsic structural and functional differences of cortical gyri and sulci (Chen et al, 2013; Deng et al, 2014; Fischl and Dale, 2000; Jiang et al, 2015; Nie et al, 2012; Zeng et al, 2015; Zhang et al, 2014). For instance, the cortical thickness on gyri is generally larger than that on sulci in adults (Fischl and Dale, 2000) and in developing infants (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%